1-Cyclohexyl-5-(2-hydroxybenzoyl)-3-nitropyridin-2(1H)-one - T. Siva Ranjani; N. Poomathi; G. Vimala; Paramasivam T. Perumal; K. Sakthi Murugesan (IUCrData, 2017)
In the title compound, C18H18N2O5, the cyclohexane ring adopts a chair conformation, and its mean plane is almost normal to the central pyridin-2-one ring with a dihedral angle of 87.94 (8)°. The latter ring is inclined to the 2-hydroxybenzoyl ring by 50.92 (8)°. There is an intramolecular O—H...O hydrogen bond in this unit forming an S(6) ring motif. The NO2 group is disordered over two orientations of equal occupancy. In the crystal, molecules are linked via C—H...O hydrogen bonds, forming chains propagating along [001]. Inversion-related chains are linked by C—H...π interactions, forming columns along the c-axis direction.